Simplify y^2 + 8y + 25?

I cant figure out two numbers that add up to 8 and multiply to 25.

Help.

Update:

Sorry! I meant factor.

6 Answers

Relevance
  • Dr Pi
    Lv 4
    1 decade ago
    Favorite Answer

    y² + 8y + 25 Plug into quadratic formula: (-b±√(b²-4ac))/(2a) where ax² + bx + c = 0

    = (-8±√((-8)²-(4)(1)(25))/(2(1))

    = (-8±√(-36))/(2)

    = (-8±6i)/(2)

    = -4±3i

    = -4+3i & -4-3i

    Change to factors by subtract these #'s from y

    (y-(-4+3i))(y-(-4-3i))

    = (y+4-3i)(y+4+3i)

    ANSWER: (y+4-3i)(y+4+3i)

    To check answer plug in a # & see if they both come out to be the same. I'll plug in 5 for y.

    (5)^2 + 8(5) + 25

    = 25 + 40 + 25

    = 90

    (5+4-3i)(5+4+3i)

    = (9-3i)(9+3i)

    = 81 + 27i - 27i - 3i²

    = 81 + 9

    = 90

  • 1 decade ago

    There are no two numbers that add up to 8 and multiply to 25

    So you must complete the square

    (y² + 8y + 16) + 25 - 16

    (y + 4)² + 9

  • 1 decade ago

    There are no two numbers that add up to 8 and multiply to 25 so you must

    Complete the square

    (y² + 8y + 16) + 25 - 16

    (y + 4)² + 9

  • JOS J
    Lv 7
    1 decade ago

    25 + y (8 + y)

  • How do you think about the answers? You can sign in to vote the answer.
  • Anonymous
    1 decade ago

    y^2 + 8y + 25 = 0

    this is a second degree equation so it must have 2 solutions

    solution number 1:

    y = - 8 + sqrt ( 64 - 100) / 2

    y = - 8 + sqrt (-36) / 2

    y = -8 + 6i / 2

    y = - 4 + 3i

    where i = sqrt (-1)

    now lets pretend that solution n. 1 (-4 + 3i) equals = a

    solution number 2:

    y = - 8 - sqrt ( 64 - 100) / 2

    y = - 8 - sqrt (-36) / 2

    y = -8 - 6i / 2

    y = - 4 - 3i

    now lets pretend that solution n. 2 (-4 - 3i) equals = b

    ---

    when you have

    (y-a)(y-b)

    y equals = + a and + b

    so let's exchange a and b with the solutions of the previous equation

    ( y - ( - 4 + 3i ) ) ( y - ( - 4 - 3i ) ) = 0

    (y+4-3i)(y+4+3i)=0 <----------------------- THIS IS THE ANSWER

  • 1 decade ago

    Umm I don't know if I'm right but here is what I got:

    y^2 + 8y = -25

    (y + 16)^2 = -25 + 16

    y + 16 = +\-3

    y = -13 or 19

Still have questions? Get your answers by asking now.